Dual media cinematography - Mclntyre, D. R.; Hay, J. G. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
Swimming is an activity in which the performer spends some time with his body completely immersed in the air and some time with it completely immersed in water. However, the vast majority of the time is spent with his body moving simultaneously in both the air and water near the interface between these two media. It follows that anyone concerned with completely observing and evaluating a swimming performance must of necessity obtain an impression of the total performance. There is an obvious need, therefore, for some means of simultaneously recording the actions which take place above and below the water. It is conceivable that two high speed motion picture cameras could be used for this purpose-with one camera above and one below the water level. However, because of the problems associated with accurately synchronizing the two ftlm records, there would appear to be some advantage in using a technique which simultaneously records the above-andbelow-water level action on the same film frame. It is the purpose of this paper to describe such a technique.